Development of e-modules based on local wisdom to improve Junior High School student learning outcomes in science learning - Adeningsih, Sri Astika; Ntobuo, Nova Elysia; Umar, Masri Kudrat; Abdjul, Tirtawaty (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2024)
This research aims to produce a product in the form of a learning E-module, namely an E-module based on local wisdom. Then a validation test was carried out to determine the feasibility and quality of the local wisdom-based e-module. This type of research is development research or Research and Development (R&D) with the ADDIE model which consists of stages, namely analysis, design, development, implementation and evaluation. Data collection techniques are by means of interviews, observations, and questionnaires. The validation test results obtained an average of 3.62 which was interpreted into the valid or appropriate category. Student respondents to the e-module obtained a percentage result of 86.11% in the very good category. As well as achieving a percentage of student activities of 84.5% in the good category. Based on the data that has been obtained, it can be concluded that the local wisdom-based e-module has met the criteria of being valid, practical, effective and therefore suitable for use in science learning at school.